Kedokteran Gigi Pencegahan dalam Bidang Periodonsia, Konservasi Gigi, Prostodonsia dan Ortodonsia - Budi Budi; Dendy Dwirizky Gunawan; William Wijaya; Yufridika Yufridika (Universitas Muhammadiyah Manado, 2024)
Understanding of the etiology of oral cavity disease in various fields of science has increased. These improvements are demonstrated in various studies conducted to increase the success of treatment. However, preventive intervention strategies are not sufficient to reduce the number of populations with oral cavity diseases. Adequate prevention can reduce morbidity and treatment costs for disease. The aim of writing this article is to increase clinician's understanding of oral disease prevention strategies, both in the fields of periodontics, dental conservation, prosthodontics and orthodontics